Colon capsule endoscopy is a viable alternative to colonoscopy for the investigation of intermediate- and low-risk patients with gastrointestinal symptoms: results of a pilot study - Mc Namara, Deirdre (My University, 2021)
Background and study aims: Colon capsule endoscopy (CCE) is a recommended viable alternative to colonoscopy for colonic visualisation in a variety of clinical settings with proven efficacy in polyp detection, surveillance, screening and Inflammatory Bowel Disease (IBD) assessment. CCE efficacy in an unselected average risk symptomatic cohort has yet to be established. The aim of this study was to determine the feasibility of CCE imaging assessment in average risk symptomatic patients as an alternative to colonoscopy with and without additional biomarker assessment. Patients and methods: This was a prospective, single-center comparison study of colonoscopy, CCE and biomarker assessment. Results: Of 77 invited subjects, 66 underwent both a CCE and colonoscopy. A fecal immunochemical test (FIT) and fecal calprotectin (FC) were available in 56 and 59 subjects. In all 64 % (n = 42) had any positive finding with 16 (24 %) found to have significant disease (high-risk adenomas, IBD) on colonoscopy. The CCE completion rate was 76 %, five (8 %) had an inadequate preparation, the CCE polyp detection rate was high at 35 %. The sensitivity, specificity, positive and negative predictive values of CCE for significant disease were 81 %, 98 %, 93 % and 94 % respectively. In addition, three (5 %) significant small bowel diagnoses were made on CCE. FC and FIT were frequently elevated in patients with both colitis (5/7, 71 %) and high-risk adenomas (4/7 57 %). While both had a low positive predictive value for clinically significant disease, FIT 32 % and FC 26 %. Conclusions: CCE is a safe and effective alternative to colonoscopy in symptomatic average risk patients with or without the addition of biomarker screening.
PUBLISHED
Keywords: Capsule Endoscopy; colon capsule endoscopy; Health